THE RELATIONSHIP BETWEEN WORK MOTIVATION AND THERAPEUTIC COMMUNICATION APPLICATION AT A PRIVATE HOSPITAL IN JAKARTA - Puput Melani Bode; Roma Gultom; Rosari Nababan; Belet Lydia Ingrit; Tirolyn Panjaitan (Universitas Pelita Harapan, 2021)
The role of communication cannot be separated from the application of nursing care process because it can influence patients’ satisfaction on nurses’ care in the hospital. Therapeutic communication has not been applied well by nurses, hence there is a lack of trust among nurse and patient’s relationship. This study aimed to identify the relationship between nurses’ work motivation and nurses’ therapeutic communication toward patients in ward at a private hospital in Jakarta. This study used a quantitative method, a descriptive correlational design and a cross-sectional approach. A Chi-Square test was applied to identify the relationship between both variables. The population of this study were all of the nurses who work in the ward (40 nurses) and the, sampling technique of this study was a total sampling method. The result of the study showed that nurses’ work motivation was categorized as high (57.5%) and the application of the therapeutic communication was in the highest category (60%). The result of the chi-square test showed that nurses’ work motivation was related to the therapeutic communication application with p-value 0.001(p<0.05). Thus, the higher work motivation of nurse, the better the application of communication therapeutic. In relation to the recommendation for further research, the researchers suggest examining other factors related to the implementation of therapeutic communication.